Software testing : an ISEB intermediate certificate - Hambling, Brian, 1946- (British Informatics Society, 2009)
Covering testing fundamentals, reviews, testing and risk, test management and test analysis, this book helps newly qualified software testers to learn the skills and techniques to take them to the next level. Written by leading authors in the field, this is the only official textbook of the ISEB Intermediate Certificate in Software Testing.